Lending Money, Generating Vulnerabilities: Between the Theories of Social Reproduction, Sex Work and Microfinance in Cambodia (Journal of Applied Business and Economics, 2020)
Applying social reproduction feminist theory for exploring the interconnections between capitalism and women’s exploitation, this paper analyses how the patriarchal system operates for the reproduction of vulnerable women, specifically as a source of (capital) accumulation. It assesses the effects that microfinance has on social reproduction and sex work. As the Cambodian case demonstrates, microfinance has oftentimes reinforced gender structures generating a widespread over-indebtedness and augmenting the likelihood for women to enter the sex industry. Working within a debt-driven finance perpetuating the subjection of women into exploiting practices, microfinance may ultimately deprive the nation of vital human resources for economic development.
Keywords: Business; Economics; social reproduction; Cambodia; financialisation; micro-finance; political economy of development; gender inequalities